Botanical essential oils and uses as mosquitocides and repellents against dengue. (April 2018) - Chellappandian, Muthiah; Vasantha-Srinivasan, Prabhakaran; Senthil-Nathan, Sengottayan; Karthi, Sengodan; Thanigaivel, Annamalai; Ponsankar, Athirstam; Kalaivani, Kandaswamy; Hunter, Wayne B.
Abstract: Plants naturally produce bioactive compounds along with many secondary metabolites which serve as defensive chemical against herbivorers including insect pests. One group of these phytochemicals are the 'Essential Oils' (EO's), which possess an extensive range of biological activity especially insecticidal and insect repellents. This review provides a comprehensive viewpoint on potential modes of action of biosafety plant derived Essential Oils (EO's) along with their principal chemical derivatives against larvae and adult mosquito vectors of dengue virus. The development and use of Essential Oils (EO's) effectively applied in small rural communities provides an enormous potential for low cost effective management of insect vectors of human pathogens which cause disease. Highlights: Essential Oils' (EO's), which possess an extensive range of biological activity especially insecticidal and insect repellents. The development and use of Essential Oils (EO's) effectively applied in small rural communities provides an enormous potential for mosquito disease control. Natural plant-derived EO product-based, innovation and development represents a complex enterprise requiring increased organization and standardization.